Catch Composition and Selectivity of Fishing Gears in a Multi-Species Indonesian Coral Reef Fishery - Humphries, Austin T.; Gorospe, Kelvin D.; Carvalho, Paul G.; Yulianto, Irfan; Kartawijaya, Tasrif; Campbell, Stuart J. (Frontiers in Marine Science, 2019)
There are millions of small-scale fishers worldwide that rely on coral reefs for their livelihood. Yields from many of these coral reef fisheries, however, have been declining. In Indonesia and other coral reefs worldwide, management approaches are dominated by marine protected areas but other options including gear-restrictions may be feasible and more adaptive to local ecological and social conditions. Yet, there is little data on the impacts and selectivity of fishing gears for coral reef fisheries. In this paper we present results from a case study on the island of Lombok where we examine the selectivity and overlap in catch composition of the two main fishing gear types: spearguns and handlines. The catch per unit effort was greater in handlines than spearguns, 10.8 and 9.97 kg trip-1 respectively. The two gears targeted different fish communities with little overlap in dominant species, suggesting a partitioning of resources; handlines targeted piscivores whereas spearguns targeted mostly herbivores. Mean trophic level was 3.6 for the handline catch and 2.8 for spearguns where it was inversely related to catch per unit effort. Spearguns captured more species overall and the number of species increased as the catch per unit effort increased. Length parameters of maturity indicated that neither gear showed signs of (growth) overfishing and fishing grounds dominated by speargun fishers had catches associated with younger ages at first maturity than handlines. Our findings provide local baseline data on the potential utility of gear restrictions as a management tool. Specifically, managers could monitor reefs and reduce handlines when piscivorous fishes are low and on spearguns when species diversity is low or algal abundance is high. Should it become more desirable to implement ecosystem approaches to management that are adaptive to changing ecological and social conditions, these indicators may be used as starting points along with local management preferences of fishers.